Investigation of the FCNC Processes in the 3-4-1-1 Model - Huong, D. T.; Thuy, L. X.; Nhuan, N. T.; Phuong, H. T. (Communications in Physics, 2021)
We study the FCNC problems in 3-4-1-1 model in a way different from the previous work. The sources of FCNC at the tree-level in the 3-4-1-1 model come from both the gauge and scalar sectors. We show that the most stringently bound on the tree-level FCNC interactions comes from the meson oscillations. The lower bound on the new physics scale is imposed more tightly than in the previous work, \(M_{new} > 22\) TeV. On the allowed value domain of the new physical scale, we show that the contribution of the tree-level FCNC interactions to the BrB\(_s → μ^+ μ^-)\) is negligible.